Simultaneous quantification of protein–DNA contacts and transcriptomes in single cells - Rooijers, Koos; Markodimitraki, Corina M.; Rang, Franka J.; de Vries, Sandra S.; Chialastri, Alex; de Luca, Kim L.; Mooijman, Dylan; Dey, Siddharth S.; Kind, Jop (Nature biotechnology, 2019)
Protein–DNA interactions are critical to the regulation of gene expression, but it remains challenging to define how cell-to-cell heterogeneity in protein–DNA binding influences gene expression variability. Here we report a method for the simultaneous quantification of protein–DNA contacts by combining single-cell DNA adenine methyltransferase identification (DamID) with messenger RNA sequencing of the same cell (scDam&T-seq). We apply scDam&T-seq to reveal how genome–lamina contacts or chromatin accessibility correlate with gene expression in individual cells. Furthermore, we provide single-cell genome-wide interaction data on a polycomb-group protein, RING1B, and the associated transcriptome. Our results show that scDam&T-seq is sensitive enough to distinguish mouse embryonic stem cells cultured under different conditions and their different chromatin landscapes. Our method will enable the analysis of protein-mediated mechanisms that regulate cell-type-specific transcriptional programs in heterogeneous tissues. scDamID&T combines DNA adenine methyltransferase-based labeling of protein–DNA contact sites with transcriptome sequencing to analyze regulatory programs in single cells.